Effect of nanocatalyst modification on concrete strength - SHYSHKINA, Oleksandra; SHYSHKIN, Oleksandr (Ways to Improve Construction Efficiency, 2024)
The article presents the results of the analysis of the properties of materials based on Portland cement, polyalcohols and surfactants used in ultra-low doses, describes the results of determining the effect of ultra-low doses of glycerin and surfactants on the strength of concrete. The aim of the work is to determine the effectiveness of the use of a mixture of glycerin and surfactants in ultra-low doses during the hardening of Portland cement. The methodology of the experiments includes the following methods: analysis of studies on the use of glycerin and surfactants; standard concrete test methods; comparative analysis; systematization and generalization of foreign and domestic experience. As a result of the study, the effect of a mixture of glycerin and surfactants applied in ultra-low doses to the strength of concrete. It has been proven that in this case, the action of ultra-small doses of a mixture of glycerin and surfactants is to reduce the number of open pores in the cement stone. Experimental studies have confirmed that surfactant molecules such as hyperplasticizers or others significantly alter the pH of the water used to make concrete. Increasing the mechanical strength of the resulting concrete makes it possible to replace part of the cement with a nanopowder made of a cheaper mineral. It has been found that an increase in the water-cement ratio in a mixture of glycerol and surfactants leads to an increase in the efficiency of ultra-low doses of surfactants substances in the formation of concrete compressive strength. The highlighted scientific materials became the starting point for understanding the issue under study. The effect of ultra-low doses of glycerin and surfactants on the strength of concrete has been identified and substantiated. The results of the study can be used in the production of concrete and reinforced concrete products and structures.